2016
DOI: 10.1038/nrneurol.2016.90
|View full text |Cite
|
Sign up to set email alerts
|

The question of alteplase dose for stroke is not resolved

Abstract: Welfare approved the use of the tissue plasminogen activator (tPA) alteplase for acute stroke at a dose of 0.6 mg/ kg within 3 h of onset, a lower dose than the standard of 0.9 mg/kg in Europe and the USA. The approval of this low dose was based on results of the Japan Alteplase Clinical Trial (J-ACT) 1 ; in this trial, the administered dose of 0.6 mg/kg alteplase was selected on the basis of previous studies that showed 0.6 mg/kg to be noninferior to 0.9 mg/kg in Japanese patients. The recently published Enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[18][19][20] Since the approval of IVT for the treatment of ischemic stroke by the FDA in 1996, there has been a debate about the benefit and potential harm of IVT administration and about the optimal treatment candidate selection. [21][22][23][24][25][26][27] A previous comprehensive meta-analysis of individual patient data from randomized trials observed that IVT improves the overall odds of good outcomes when delivered within 4.5 hours, irrespective of age and NIHSS. 28 Regarding the degree of early ischemic changes, previous landmark trials evaluating the effect of IVT excluded patients with early ischemic changes in >1/3 of the MCA territory, while other studies concluded not to have enough statistical power to ascertain whether IVT adds risk or benefit (i.e., in patients with ASPECTS 0-7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Since the approval of IVT for the treatment of ischemic stroke by the FDA in 1996, there has been a debate about the benefit and potential harm of IVT administration and about the optimal treatment candidate selection. [21][22][23][24][25][26][27] A previous comprehensive meta-analysis of individual patient data from randomized trials observed that IVT improves the overall odds of good outcomes when delivered within 4.5 hours, irrespective of age and NIHSS. 28 Regarding the degree of early ischemic changes, previous landmark trials evaluating the effect of IVT excluded patients with early ischemic changes in >1/3 of the MCA territory, while other studies concluded not to have enough statistical power to ascertain whether IVT adds risk or benefit (i.e., in patients with ASPECTS 0-7).…”
Section: Discussionmentioning
confidence: 99%
“…Since the approval of IVT for the treatment of ischemic stroke by the FDA in 1996, there has been a debate about the benefit and potential harm of IVT administration and about the optimal treatment candidate selection 21–27 . A previous comprehensive meta‐analysis of individual patient data from randomized trials observed that IVT improves the overall odds of good outcomes when delivered within 4.5 hours, irrespective of age and NIHSS 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Since approval of IVT for the treatment of ischemic stroke by the FDA in 1996, there has been an ongoing debate about harm and benefit of IVT administration and about the optimal treatment selection [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In 2018, the WAKE-UP trial reported a beneficial treatment effect of IVT compared to placebo despite a slightly increased rate of sICH [ 34 ].…”
Section: Discussionmentioning
confidence: 99%